The Readiness of Teaching English to Young Learners in Indonesia - Mutiah, Syifa Dwi; Nakhriyah, Minkhatun; HR, Nida Husna; Hidayat, Didin Nuruddin; Hamid, Farida (Jurnal Basicedu, 2020)
This study attempted to investigate teachers, students, and schools' readiness in conducting English programs for young learners in Indonesia. Therefore, the participants of this study were from three aspects, as mentioned above. There were two levels of schools involved in this study. Those were elementary and pre-school levels consisted of 10 elementary school teachers, pre-school teachers, elementary and preschool students, elementary and pre-school schools in several areas of Indonesia. The data were collected through the questionnaire and focused on their readiness to conduct English at their level. This study showed that students’ readiness to learn English was very high even though they often encounter obstacles or difficulties in the process of learning English in class. Meanwhile, facilities readiness to support the teaching-learning English process was not fully complete; the conditions and facilities were limited. On the other hand, the teacher readiness was high, although they lack confidence in using English in the classroom, and it was found that the teacher's educational background became one of the reasons. Additionally, teacher training was stated to be needed to develop their professionalism. However, they also stated that they had not joined that training yet. Therefore, less professional development training became a factor in decreasing the teacher readiness to teach at elementary and kindergarten levels.